The impact of rule modifications on player behaviour in a talent identification and development environment: A case study of the Rugby Football Union's Wellington Academy Rugby Festival. Issue 23 (1st December 2020) - Ashford, Michael; Burke, Kate; Barrell, Donald; Abraham, Andrew; Poolton, Jamie
ABSTRACT: Research has suggested that competition within talent identification and development systems should be modified from the adult format of the sport to meet the developmental needs of those participating. Yet limited research has evaluated the success of game changes, particularly the effectiveness of modifying the rules of a game to purposefully engineer changes in player behaviour. The purpose of this study was to monitor the impact of rule modifications on player behaviour within a talent identification and development system in rugby union. Performance indicators (ball in play, pass, offload, kick) were collected during full length (70 min) and shortened durations (30–42 min) of competitive matches played during a weeklong under sixteen rugby union festival in 2016 and after rule modifications were introduced in 2017–2019. The findings indicate that rule modifications had the prescribed impact on player actions, particularly in the shortened duration formats of the game. Therefore, rule modifications provide talent developers a tool to manipulate player behaviour, in this case skill attempts, within full-sided competitive matches.